3D atomic imaging of low-coordinated active sites in solid-state dealloyed hierarchical nanoporous gold. Issue 45 (9th November 2021) - Wang, Chunyang; Liu, Hongyang; Duan, Huichao; Li, Zhenwei; Zeng, Panlin; Zou, Peichao; Wang, Xuelu; Ye, Hengqiang; Xin, Huolin L.; Du, Kui
Abstract : 3D imaging of low-coordinated atoms in nanoporous metal by atomic-resolution electron tomography. Abstract : Boosting the activity of catalysts by constructing abundant low-coordinated sites is of considerable interest for maximizing the efficiency of catalysts. Equally importantly, three-dimensional imaging of these low-coordinated sites is crucial to the fundamental understanding of the relationship between the coordination environment and catalytic performance. Herein, we fabricate a novel class of hierarchical nanoporous gold which is rich in low-coordinated sites through solid-state plasma dealloying. For the first time, by using atomic-resolution electron tomography, we map out the coordination environment of the hierarchical nanoporous gold in three dimensions at the single-atom level. Quantitative coordination analysis reveals that owing to the introduction of substantial low-coordinated active sites with coordination numbers from 5 to 7, the catalytic performance of the hierarchical nanoporous gold in CO oxidation is improved. Our work provides in-depth insights into the relationship between the catalyst's coordination environment and catalytic performance, and the proof-of-concept demonstrated in this study is expected to be generally applicable to the design and study of a broad range of catalysts.